Epigenetic activation during T helper 17 cell differentiation is mediated by Tripartite motif containing 28 - Jiang, Yu; Liu, Ying; Lu, Huiping; Sun, Shao-Cong; Jin, Wei; Wang, Xiaohu; Dong, Chen (Nature communications, 2018)
Epigenetic regulation is important for T-cell fate decision. Although STAT3 is known to initiate Th17 differentiation program, the downstream mechanism is unclear. Here we show that Tripartite motif containing 28 ( Trim28 ) expression in Th17 cells is required for Th17-mediated cytokine production and experimental autoimmune diseases. Genome-wide occupancy analysis reveals that TRIM28-bound regions overlap with almost all Th17-specific super-enhancers (SE), and that those SEs are impaired by the deficiency of STAT3 or TRIM28, but not of RORγt. Importantly, IL-6-STAT3 signaling facilitates TRIM28 binding to the Il17-Il17f locus, and this process is required for epigenetic activation and high-order chromosomal interaction. TRIM28 also forms a complex with STAT3 and RORγt, and promotes the recruitment of RORγt to its target cytokine genes. Our study thus suggests TRIM28 to be important for the epigenetic activation during Th17 cell differentiation, and prompts the potential use of epigenetic interventions for Th17-related autoimmune diseases. T help 17 (Th17) cells are important mediators for both protective and pathogenic immune reactions, but how their functions are regulated at the epigenetic level is not understood. Here the authors show that TRIM28, a cofactor for transcriptional regulation, is important for epigenetic activation of Th17-related gene loci during Th17 response.